THE IMPROVEMENT OF A BEGINNING TEACHER SUPPORT PROGRAM TO ENHANCE TEACHER RETENTION - Patrick, Ervin D. (East Carolina University, 2018)
This study was designed to improve the current beginning teacher support program and address the problem of beginning or early career teachers leaving the district. Researchers have found that as many as 50% of teachers leave the profession within their first five years of teaching (Darling-Hammond & Sykes, 2003). This study proposed changes to the Beginning Teacher Support Program that would positively impact the turnover rate. The study focused on Craven County Schools, located in eastern North Carolina. The district has experienced three consecutive years of teacher turnover greater than 15%, causing a high degree of concern within the district. This improvement study was conducted following a small-scale proof of concept in an elementary school within the district. Supporting this study is the model of improvement offered by Langley et al. (2009), joined with the methodology of Improvement Science. There were five improvement strategies implemented in the school during the study including: (a) mentor beginning teachers through years four to six, (b) employ an experienced Exceptional Children's teacher as a beginning teacher mentor, (c) assign buddy teachers in the same subject as the beginning teacher, (d) employ additional beginning teacher mentors and (e) implement mentor and beginning teacher support meetings. The goal of this study and the implementation of these strategies was to reduce teacher turnover to 10% in the school. Although the goal was not reached during the current school year, at the conclusion of the study, the improvement strategies were deemed effective and comprehensive enough for a large-scale implementation across the district.
Keywords: education; teacher retention; teacher recidivism; recidivism; beginning teacher support program; beginning teacher support; mentor; beginning teacher mentor; teacher support; Teacher turnover--North Carolina--Craven County; School improvement programs--North Carolina--Craven County; Elementary school teachers--North Carolina--Craven County--Attitudes; First year teachers--In-service training--North Carolina--Craven County